2014
DOI: 10.3109/13880209.2013.865243
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester promotes anti-inflammatory effects by inhibiting MAPK and NF-κB signaling in activated HMC-1 human mast cells

Abstract: In activated HMC-1 cells, pretreatment with CAPE decreased the phosphorylation of c-Jun N-terminal kinase. In addition, CAPE inhibited PMACI-induced nuclear factor (NF)-kB activation by suppressing IkBa phosphorylation and its degradation. Discussion and conclusion: Our results indicated that CAPE can modulate mast cell-mediated allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…Flavonoids and caffeic acid also aid the immune system by promoting phagocytic activities and stimulating cellular immunity. 7,23,24,25 During the inflammatory reaction, activated macrophages will produce TNF-α, IL-1, IL-6, IL-10, chemokines, and short-lived lipid mediators to orchestrate a local inflammation. 26 Studies have shown significant increase in TNF-α and IL-1 in irreversible pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids and caffeic acid also aid the immune system by promoting phagocytic activities and stimulating cellular immunity. 7,23,24,25 During the inflammatory reaction, activated macrophages will produce TNF-α, IL-1, IL-6, IL-10, chemokines, and short-lived lipid mediators to orchestrate a local inflammation. 26 Studies have shown significant increase in TNF-α and IL-1 in irreversible pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…CAPE is considered a particularly strong anti-inflammatory constituent, able to specifically target NF-κB signaling (Armutcu et al, 2015). This compound has been also found to modulate ERK MAPK signaling in T cells and mastocytes (Cho et al, 2014), and to regulate PI3K/Akt pathway in different human cell lines (Li et al, 2017). Possible downstream effects of these anti-inflammatory mechanisms may include the downregulation of key inflammatory enzymes, like xanthine oxidase, cyclooxygenase, matrix metalloproteinases, and inducible nitric oxide synthase (Armutcu et al, 2015; Li et al, 2017).…”
Section: Propolismentioning
confidence: 99%
“…Among the inflammatory mediators released from mast cells, histamine is known to be the most well-characterized mediator implicated in the acute phase of hypersensitivity, including anaphylactic shock (30). To determine whether BV inhibits histamine release in the culture medium from mast cells, the PMAcI-induced histamine release was measured.…”
Section: Resultsmentioning
confidence: 99%